Useful Captives : The Role of POWs in American Military Conflicts - Foote, Lorien, 1969-; Krebs, Daniel (Book collections on Project MUSE., 2021)
"Military history often focuses on heroes - soldiers of high and low ranks who took decisive action, won wars, and decided battles. Prisoners of war, however, do not always fit this heroic narrative. They did not win on the battlefield and, especially in the eyes of a nationalistic audience in the nineteenth and twentieth century, they had not given everything, even their lives, to their cause or country. As a result, captive soldiers have often been treated as a separate topic in military history - disconnected from the larger and seemingly more important story of planning and conducting warfare and the societies that waged it"--